Dynamic MicroRNA-Expression in Plasma of Melanoma Patients Correlates With Progression, PD-L1 Status and Overall Survival - Sarah, Degenhardt; Marc, Bender; I-Peng, Chen; Stefan, Henning; Mouna, Mhamdi-Ghodbani; Christin, Starzonek; Peter, Mohr; Christoffer, Gebhardt; Klaus, Pantel; Beate, Volkmer; Rüdiger, Greinert (Journal of Cancer Genetics And Biomarkers, 2024)
Melanoma treatment has improved significantly with the development of immune checkpoint inhibition (ICI), which has greatly enhanced the survival rates of patients with metastatic melanoma. However, a significant number of patients do not respond well to ICI treatment and experience progression. This highlights the critical need for practical means to track melanoma patients' response to ICI. To address this issue, the patterns of circulating miRNAs were studied in liquid biopsies of melanoma patients. These miRNAs have the potential to provide essential information regarding the cancer stage, progression, and the presence of PD-L1 in tumor tissue. A sophisticated flow cytometric test was used to measure up to 63 different miRNAs at once. The study identified a combination of nine miRNAs that are capable of distinguishing between different stages of melanoma, particularly stage IV. Additionally, five miRNAs were pinpointed which are downregulated in patients who do not respond to ICI treatment. Furthermore, two miRNAs were found that correlate to the level of PD-L1 in tumor tissue, and low levels of miR-150-5p were linked to poorer overall survival. These findings suggest that circulating miRNAs could serve as valuable markers to predict the effectiveness of ICI, provide insights into the cancer's stage and PD-L1 status, and ultimately help physicians make better treatment decisions in the future. However, further research is needed to confirm these findings and establish their clinical usefulness.
Keywords: biomarker; immune checkpoint inhibition; liquid biopsy; melanoma; microRNA; PD-L1